The Paradox of the Philatelic Business: Turning a Private Collection into a Professional Trade - Grijp, Paul (Material Culture Review)

(untitled) (National Museums of Canada, 2012)
Abstract Money plays a crucial part in the popular hobby known as philately. Most professional dealers in the world of philately used to be amateur philatelic collectors. Moreover, many professional dealers continue to expand their personal philatelic collection in some way. Not only are there various dealers, there are also different kinds of philatelic collectors. In trying to understand collectors’ motivations, we should refrain from simplistic, reductionist, mono-causal explanations, and so I propose a configurational model that combines psychological, sociological, economic and educational motives. I suggest that, among dealers, the motivation of education (learning and transmitting knowledge related to the collection), combined with the other motivations, continues to play an important part. The conclusion deals with changes in the contemporary philatelic market.